2013
DOI: 10.2337/db13-0264
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial Substrate Availability and Its Role in Lipid-Induced Insulin Resistance and Proinflammatory Signaling in Skeletal Muscle

Abstract: The relationship between glucose and lipid metabolism has been of significant interest in understanding the pathogenesis of obesity-induced insulin resistance. To gain insight into this metabolic paradigm, we explored the potential interplay between cellular glucose flux and lipid-induced metabolic dysfunction within skeletal muscle. Here, we show that palmitate (PA)-induced insulin resistance and proinflammation in muscle cells, which is associated with reduced mitochondrial integrity and oxidative capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…7, 9 In the present study, although preexisting obesity alone had a minor impact on mitochondrial biogenesis, it was predominant in Obese-HT, where HT suppressed mitochondrial function most prominently, underscoring the detrimental interaction of obesity with HT. While systemic oxidative stress remained unchanged, local oxidative stress (myocardial dihydroethidium) evoked by the co-existence of diet and HT can increase nitric oxide degradation 17 or decrease its production, 18 and in turn reduce mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…7, 9 In the present study, although preexisting obesity alone had a minor impact on mitochondrial biogenesis, it was predominant in Obese-HT, where HT suppressed mitochondrial function most prominently, underscoring the detrimental interaction of obesity with HT. While systemic oxidative stress remained unchanged, local oxidative stress (myocardial dihydroethidium) evoked by the co-existence of diet and HT can increase nitric oxide degradation 17 or decrease its production, 18 and in turn reduce mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 44%
“…Nevertheless, energy production becomes less efficient, as overloaded mitochondria undergo stress and develop dysfunction. 7, 8 High-fat diet has been shown to decrease mitochondrial biogenesis, reduce mitochondrial coupling efficiency, and impair ATP synthesis. 911 These findings suggest that mitochondrial homeostasis can be modulated by energy supply and potentially impact cardiac health and function.…”
Section: Introductionmentioning
confidence: 99%
“…This key relationship is exemplified by the finding that long-chain saturated fatty acids such as palmitate (C16:0), whose circulating levels become elevated in the obese state, act to promote insulin resistance and metabolic impairment, whereas they are predominantly degraded through mitochondrial ␤-oxidation (13,70,77). Accordingly, various indicators of reduced mitochondrial density and/or oxidative capacity have been reported in skeletal muscle and adipose tissue isolated from insulin-resistant and/or obese human subjects (51,67,118).…”
Section: Regulation Of Energy Metabolism: the Role Of Mitochondriamentioning
confidence: 99%
“…Furthermore, lipid infusion and/or high-fat feeding in humans and rodents has been shown to reduce ATP synthesis, oxygen consumption, and oxidative phosphorylation capacity (17,24,134). In addition, reductions in the levels of peroxisome proliferator-activated receptor (PPAR)␥ coactivator (PGC)-1␣, a key transcriptional coordinator of mitochondrial biogenesis, may also contribute to free fatty acid (FFA)-induced mitochondrial dysfunction and loss of insulin sensitivity (25,51,77). Collectively, these observations support the idea that reduced mitochondrial density and/or oxidative capacity (associated with lipid oversupply) may restrict FFA utilization, thereby permitting the accumulation of lipotoxic intermediates such as ceramide and diacylglycerol (DAG), which have been implicated in the pathogenesis of insulin resistance (50,68,152,157).…”
Section: Regulation Of Energy Metabolism: the Role Of Mitochondriamentioning
confidence: 99%
“…Apart from becoming apoptotic, cells loaded with FFA also show impairment in FAO and glucose uptake. Excess FFA leads to 'lipotoxicity' by the intracellular accumulation of triglyceride (TG), ceramides and other fatty acid derivatives that impair mitochondrial β-oxidation and insulin resistance in skeletal muscle [20][21][22][23]. Recent studies have shown modulation of cytosolic ceramides through altered ceramide synthase expression improves insulin sensitivity [24].…”
Section: Introductionmentioning
confidence: 99%